As concepções de professores formadores em relação ao uso da história da matemática no processo ensino aprendizagem nos cursos de licenciatura em matemática - SILVA, Johnattan Amorim da (Universidade Federal do Pará, 2011)
The objective of this research is to investigate the conceptions of teachers-trainers of Mathematics teachers with relation to History of Mathematics in the teaching learning process in order to understand which ideas and methodologies these teacherstrainers use when are about historical approaches or to teach History of Mathematics subjects. In order to this was carried out a quality research with using of semistructured interviews with a nine teachers group that teach classes in Higher Education institutions, in particular in Mathematics Undergraduate Courses. To analyze these teachers speeches, our research subjects, we find to understand their conceptions and practical experiences are about the History of Mathematics. Were adopted three analysis categories using the teachers interviews: First Contacts with History of Mathematics; Learning Strategies and Pedagogical Potentiality; and Obstacles of using of History of Mathematics. In the first category there were significant differences, the five teachers have argued that they have not kept any contact with the History of Mathematics while graduation studentes and the others four teachers have had contact only in one subject gone with of only certain text-book. In second category we have realized that learning strategy used for the most of teachers when are about History of Mathematics is through of using of seminaries. In third category five teachers have argued the existence of obstacles. The teachers conceptions study participated of this research has pointed out the importance of History of Mathematics in the teacher education and considerations about the applicability or difficulty of using of History of Mathematics in the teaching learning and its contribuition in the mathematical and critical development of student.